IMPLEMENTASI MANAJEMEN STRATEGI BERBASIS PEMBIASAAN DALAM MENUMBUHKAN KARAKTER RELIGIUS SISWA DI SMAN 1 GALIS PAMEKASAN - Ali Nurhadi (al-Afkar, Journal For Islamic Studies, 2020)
Implementation of habituation-based management strategies in growing the religius character of students in SMAN 1 Galis Pamekasan can change the character of students more religius. The students look polite and polite in various ways. The results showed that: firstly, there was a habit-based strategy planning in growing students' religius character at SMAN 1 Galis Pamekasan, namely by involving stakeholders to develop a plan for growing religius character as outlined in curriculum documents through various extra activities and subjects. Both implementations are by activating positive religius activities, such as prayer in congregation, reading short Al-Qur'an letters and Yasin letters before learning, reading prayers before and after learning, and kissing the teacher's hand. The third evaluation in the implementation of customary-based strategy management in growing the religius character of students in SMAN 1 Galis Pamekasan is the supporting factors, namely; (1) there are similarities in School Rules, (2) there is support from Teachers and Stakeholders, and (3) there are adequate facilities. While the inhibiting factors namely; (1) there are differences in the character of students, (2) lack of attention from parents of students, and (3) the existence of negative community responses.